2012
DOI: 10.1111/j.1540-8159.2011.03314.x
|View full text |Cite
|
Sign up to set email alerts
|

Near Elimination of Ventricular Pacing in SafeR Mode Compared to DDD Modes: A Randomized Study of 422 Patients

Abstract: In this selected patient population, SafeR markedly suppressed unnecessary Vp compared with DDD modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Clinical and echocardiographic variables were as expected for a cohort of patients with an average of 10 years of RV pacing 10. Patients in AF were more likely to have symptoms (63% vs 51% in NYHA class II; χ 2 =6.0; p<0.05), larger hearts (LV end-diastolic diameter (LVEDD) 55 mm (52–57) vs 49 (46–51); p=0.003) and higher baseline NT-pro-BNP levels (1778 (IQR ng/L 2366) vs 485 (IQR 1301); p=0.003), but LVEF, past medical history and medical therapy were the same across AF and SR patients.…”
Section: Resultssupporting
confidence: 67%
“…Clinical and echocardiographic variables were as expected for a cohort of patients with an average of 10 years of RV pacing 10. Patients in AF were more likely to have symptoms (63% vs 51% in NYHA class II; χ 2 =6.0; p<0.05), larger hearts (LV end-diastolic diameter (LVEDD) 55 mm (52–57) vs 49 (46–51); p=0.003) and higher baseline NT-pro-BNP levels (1778 (IQR ng/L 2366) vs 485 (IQR 1301); p=0.003), but LVEF, past medical history and medical therapy were the same across AF and SR patients.…”
Section: Resultssupporting
confidence: 67%
“…In the meantime, this risk has been substantially reduced by the introduction of algorithms to minimize ventricular pacing (37)(38)(39) Values are n (%). *Patients in the single-chamber setting group would not have received atrial leads in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The SafeR algorithm (Sorin CRM, Clamart, France) was developed to provide a pacing mode that combines the benefits of AAI with the safety of DDD pacing . The recent randomized SaveR study confirmed the superiority of SafeR in reducing RV pacing when compared to standard DDD pacing in selected patients without high‐degree AV block and in a more general pacemaker population.…”
Section: Introductionmentioning
confidence: 99%